Identification of novel variations of oculocutaneous albinism type 2 with Prader–Willi syndrome/Angelman syndrome in two Chinese families - Chen, XiaoFei; Fang, ZiShui; Pang, Ting; Li, DongZhi; Lei, Jie; Jiang, WeiYing; Li, HongYi (Frontiers in Genetics, 2023)
Objective: Oculocutaneous albinism (OCA) is an autosomal recessive disorder caused by a variety of genomic variations. Our aim is to identify the molecular basis of OCA in two families and lay the foundation for prenatal diagnosis. Methods: Four types of OCA-causing mutations in the TYR, p, TYRP1, or SLC45A2 genes were screened. Linkage analysis was performed because the mutations found in the p gene violated the laws of classical Mendelian heredity. Primer-walking sequencing combined with microsatellite and single-nucleotide polymorphism analysis was used to ascertain deletion ranges. Bioinformatics methods were used to assess the pathogenicity of the new mutations. Results: Proband 1 was diagnosed as OCA2 with Prader–Willi syndrome (PWS) due to a novel atypical paternal deletion (chromosome 15: 22330347–26089649) and a pathogenic mutation, c.1327G>A (Val443Ile), in the p gene of the maternal chromosome. The prenatal diagnosis results for family 1 indicated the fetus was a heterozygous carrier (c.1327G>A in the p gene) with a normal phenotype. Proband 2 was diagnosed as OCA2 with Angelman syndrome (AS) due to a typical maternal deletion of chromosome 15q11-q13 and a novel mutation, c.1514T>C (Phe505Ser), in the p gene of the paternal chromosome. This novel mutation c.1514T>C (Phe505Ser) in the p gene was predicted as a pathogenic mutation. Conclusion: Our study has shown clear genotype–phenotype correlations in patients affected by distinct deletions of the PWS or AS region and missense mutations in the p gene. Our results have enriched the mutation spectrum of albinism diseases and provided insights for more accurate diagnosis and genetic counseling.